A nonlinear regression model for chicken growth data - Riazoshams, Hossein; Midi, Habshah (EuroJournals, 2009)
In this article we analyze the chicken growth data taken from chicken breeder in Marvdash in Fars Province of Iran. The chicken growth and the breeding data set can be presented as a nonlinear model with heteroscedastic errors. Six variance models are fitted to the growth data. The result of the study shows that among the six models that are considered, a variance power function model is the best fitted model for the chicken growth data.